Evaluation of Treatment and Recurrence-Free Survival in Patients with Early HER2-Positive Breast Cancer: Real-Life Data Comparing Public and Private Healthcare - Mariana Pilon Capella; Viviane Lealdini; Pedro Aguiar (Brazilian Journal of Oncology)
Introduction The present study was designed to compare the treatment provided in private and public health care facilities for women positive for early breast cancer of the human epidermal growth factor receptor 2 (HER2) subtype, who received anti-HER2 therapy in neoadjuvant or adjuvant settings, with an evaluation of the recurrence-free survival (RFS) and pathological complete response (pCR) rates.